2004
DOI: 10.5194/acp-4-1443-2004
|View full text |Cite
|
Sign up to set email alerts
|

Absolute absorption cross-section and photolysis rate of I<sub>2</sub>

Abstract: Abstract. Following recent observations of molecular iodine (I2) in the coastal marine boundary layer (MBL) (Saiz-Lopez and Plane, 2004), it has become important to determine the absolute absorption cross-section of I2 at reasonably high resolution, and also to evaluate the rate of photolysis of the molecule in the lower atmosphere. The absolute absorption cross-section (σ) of gaseous I2 at room temperature and pressure (295K, 760Torr) was therefore measured between 182 and 750nm using a Fourier Transform spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 41 publications
(37 reference statements)
5
70
0
Order By: Relevance
“…The three most recent studies (Tellinghuisen, 1973;Bauer et al, 1998;Saiz-Lopez et al, 2004) report absorption cross sections in the pressure-independent continuum (λ≤500 nm) which are in excellent agreement, differing by less than 5% at 500 nm. The present recommendation therefore adopts a reference value of σ =2.24×10 −18 cm 2 molecule −1 at 500 nm, which is the average of the values reported in the three investigations.…”
Section: Comments On Preferred Valuesmentioning
confidence: 49%
See 3 more Smart Citations
“…The three most recent studies (Tellinghuisen, 1973;Bauer et al, 1998;Saiz-Lopez et al, 2004) report absorption cross sections in the pressure-independent continuum (λ≤500 nm) which are in excellent agreement, differing by less than 5% at 500 nm. The present recommendation therefore adopts a reference value of σ =2.24×10 −18 cm 2 molecule −1 at 500 nm, which is the average of the values reported in the three investigations.…”
Section: Comments On Preferred Valuesmentioning
confidence: 49%
“…essentially in the continuum), based on a number of studies (Rabinowitch and Wood, 1936a;Tellinghuisen, 1973;Bauer et al, 1998;Saiz-Lopez et al, 2004), is well determined. Measurements in the structured region of the spectrum have been found to be very sensitive to experimental conditions, depending on the absolute concentration of I 2 and on pressure of bath gas, at the spectral resolutions typically employed.…”
Section: Comments On Preferred Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…IO was first observed at Mace Head Atmospheric Research Station (MHD), located on the west coast of Ireland, in 1997 by Long Path Differential Optical Absorption Spectroscopy (LP-DOAS) (Alicke et al, 1999) and has since been measured at a number of mid-latitude sites such as Lilia, France (Peters et al, 2005), Dagebüll, Germany (Peters et al, 2005) and Roscoff, France (Mahajan et al, 2009), with varying IO mixing ratios observed, up to a maximum of 29 ± 8.8 pptv observed by Seitz et al (2010) at Mweenish Bay just south of Mace Head on the west coast of Ireland. These previous spatially-averaged observations of IO at MHD have provided important information about the role of macroalgae in initiating iodine chemistry through the emission of molecular iodine (e.g., Saiz-Lopez and Plane, 2004) and, to a lesser extent, iodocarbons (e.g., Carpenter et al, 2001). These studies also linked iodine species to new particle formation and initiated chamber studies into the role of specific macroalgae in the emission of iodine (Bale et al, 2008;Dixneuf et al, 2009;Ball et al, 2010).…”
Section: Introductionmentioning
confidence: 94%